2008
DOI: 10.1152/ajpheart.00280.2007
|View full text |Cite
|
Sign up to set email alerts
|

Exercise enhances myocardial ischemic tolerance via an opioid receptor-dependent mechanism

Abstract: Exercise increases serum opioid levels and improves cardiovascular health. Here we tested the hypothesis that opioids contribute to the acute cardioprotective effects of exercise using a rat model of exercise-induced cardioprotection. For the standard protocol, rats were randomized to 4 days of treadmill training and 1 day of vigorous exercise (day 5), or to a sham exercise control group. On day 6, animals were killed, and global myocardial ischemic tolerance was assessed on a modified Langendorff apparatus. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 48 publications
5
48
0
2
Order By: Relevance
“…A standard exercise protocol was applied in the exercised rats similar to another study (11). Exercise groups were exposed to a running protocol for 5 days according to this protocol.…”
Section: Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…A standard exercise protocol was applied in the exercised rats similar to another study (11). Exercise groups were exposed to a running protocol for 5 days according to this protocol.…”
Section: Exercisementioning
confidence: 99%
“…This period was accepted as moderate exercise and also as a training period to prepare the animals for the last day of vigorous exercise. The vigorous exercise of the 5th day lasted 25 min at 25 m/min (11). At the end of the vigorous exercise period, the animals were killed, their hearts were harvested, and isolated hearts were perfused within 1 h after the last bout of exercise.…”
Section: Exercisementioning
confidence: 99%
“…Kısa süreli egzersizlerin kalpteki iskemi-reperfüzyon hasarı açısından pozitif yönde değişiklikler oluş-turduğu, miyokardiyal tolerans ve kan akımıyla uyarılan vazodilatasyonda artış meydana getirdiği bildirilmektedir (11,13,14). Sıçanlar üzerinde uygulanan kısa süreli egzersizler genelde 1-10 günlük bir zaman periyodunda yaptı-rılan egzersizlerdir.…”
Section: Discussionunclassified
“…Bu çalışmada egzersiz grubunda yer alan sıçanlarda daha önceki bir çalışmaya benzer bir egzersiz programı uygulandı (11). E ve E-ANP gruplarında yer alan sıçanlara koşu bandında 5 günlük bir egzersiz programı uygulandı.…”
Section: Egzersizunclassified
“…Risk of sudden cardiac death was also 2.5 times higher in athletes than those who do not exercise. 9,10 High intensity physical exercise causes an increase in myocardial oxygen demand and requires more oxygen supply, which can induce cardiac hypertrophy both physiological and pathological. 11 Animal study in rat showed that physical exercise for four days, 10 days, and 13 weeks are associated with chronic excessive pressure load on the heart that stimulates apoptosis.…”
mentioning
confidence: 99%